Phenotypic features of endometrial tumors in patients with family history of cancer - Buchynska, L.G.; Lurchenko, N.P.; Glushchenko, N.M.; Nesina, I.P. (Experimental Oncology, 2017)
Aim: To determine the peculiarities of expression of a number of proteins-regulators of the cell cycle in endometrial cancer (EC) cells in patients with a family history of oncological pathologies. Patients and Methods: 95 EC patients (stage І–ІІ) were included into the study. Clinical-genealogical analysis was performed. 54 patients (group I) had healthy relatives, and in families of 41 patients (group II) an aggregation of malignant tumors of different genesis (mainly tumors of the gastrointestinal tract and the female reproductive system) was recorded. p53, р21WAF1/CIP1, р16INK4a, and Ki-67 were assessed immunohistochemically in the surgical samples. Results: In the majority of patients, both from group I and II, moderately differentiated tumors were observed (in 38.9 and 46.3% of cases, respectively), mainly with deep myometrium invasion (64.8 and 58.5% of cases, respectively). In EC patients from group II, a significantly higher number of р16INK4a-positive cells (17.7 ± 1.7%; p = 0.001) and lower number of p53-positive (30.9 ± 3.2%; p = 0.05) and Ki-67-positive (26.9 ± 2.7%; p = 0.048) cells was observed compared to those in tumors of patients from group I (12.0 ± 1.6; 37.7 ± 2.8 and 36.7 ± 3.4%, respectively). Conclusion: Phenotypic features of the EC in the patients with family history of cancer differ from those in tumors of patients without such aggregation. The biological heterogeneity of EC seems to relate to the oncogenealogical history of patients. Also this biological heterogeneity is linked to the molecular features of EC cells, which affects cancer aggressiveness and the course of the disease.